2011
DOI: 10.1159/000323097
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Jordan: Dress Style and Gender Discrepancies

Abstract: Background/Aims: Vitamin D deficiency is highly prevalent worldwide and has been linked to many diseases. The aims of the present study were to assess the vitamin D status of Jordanians at the national level and to identify groups of the population at high risk for vitamin D deficiency. Methods: Vitamin D status was assessed in a national sample of 5,640 subjects aged ≧7 years. The study involved interviews, laboratory measurements of 25(OH)D and others, and physical measurements. The present report deals, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
102
6
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 44 publications
(30 reference statements)
15
102
6
1
Order By: Relevance
“…A previous study from Jordan has shown that the prevalence of low 25OHD status (25OHD < 30 ng/ml) was 37% in females compared to 5% in males. Dress style in the case of females was independently affecting 25OHD status; where women wearing hijab or niqab were at higher risk of low 25OHD levels than those dressed as western women [20]. Despite this finding, our results showed no significant difference in 25OHD levels between the males and females; mean 25OHD levels were 23 ng/ml (SD = 10) and 25 ng/ml (SD = 15) in the males and females, respectively.…”
Section: Vitamin D Deficiency and Night Shift Work O R I G I N A L P contrasting
confidence: 86%
See 1 more Smart Citation
“…A previous study from Jordan has shown that the prevalence of low 25OHD status (25OHD < 30 ng/ml) was 37% in females compared to 5% in males. Dress style in the case of females was independently affecting 25OHD status; where women wearing hijab or niqab were at higher risk of low 25OHD levels than those dressed as western women [20]. Despite this finding, our results showed no significant difference in 25OHD levels between the males and females; mean 25OHD levels were 23 ng/ml (SD = 10) and 25 ng/ml (SD = 15) in the males and females, respectively.…”
Section: Vitamin D Deficiency and Night Shift Work O R I G I N A L P contrasting
confidence: 86%
“…A number of factors have been found to be associated with low 25OHD levels. These factors include, among others, low sun exposure, age, obesity, smoking, dress style in the case of women and physical activity [5,[13][14][15][16][17][18][19][20]. In the absence of adequate sun exposure, 25OHD levels may be insufficient to achieve the desired physiologic role [5,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] This has been attributed to required clothing covering all skin and thereby reducing exposure to UVB. 44 In South Africa, the Mediterranean and other sun-rich areas the relevance of this study may not be immediately apparent. While individuals in sun-rich areas may be at less risk, 45 a number of studies have shown a significant prevalence of vitamin D deficiency in these areas, 46,47 potentially due to an individual's skin colour or sunscreen application.…”
Section: Discussionmentioning
confidence: 84%
“…In 2009, we conducted a national population-based study to specifically assess the vitamin D and B 12 status and metabolic disorders in Jordan [14]. In the present study, we report our findings regarding the prevalence of vitamin B 12 deficiency and its associated factors in Jordanian adults.…”
Section: Introductionmentioning
confidence: 93%